2012
DOI: 10.1038/ejhg.2011.266
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity in Centre d’Étude du Polymorphisme Humain (CEPH) pedigrees

Abstract: A set of Centre d'É tude du Polymorphisme Humain (CEPH) cell lines serves as a large reference collection that has been widely used as a benchmark for allele frequencies in the analysis of genetic variants, to create linkage maps of the human genome, to study the genetics of gene expression, to provide samples to the HapMap and 1000 Genomes projects, and for a variety of other applications. An explicit feature of the CEPH collection is that these multigenerational families represent reference panels of known r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The pedigrees were drawn from a population of primarily northern European descent which has experienced very low consanguinity (Jorde 1989), no evidence of founder effect (McLellan et al 1984), and heterozygosity similar to that of other populations of European ancestry (Xing et al 2009a). A previous study identified several related pairs of individuals in the Utah and non-Utah CEPH pedigrees (Stevens et al 2012), but only one mating pair used in our study had detectable consanguinity, with a coefficient of relationship of 0.001. Here, we present our findings of de novo L1, SVA, and Alu retrotransposition events in these pedigrees using three MEI-calling tools: MELT (Gardner et al 2017), RUFUS (https://github.com/ jandrewrfarrell/RUFUS) (Ostrander et al 2018), and TranSurVeyor (Rajaby and Sung 2018).…”
mentioning
confidence: 63%
“…The pedigrees were drawn from a population of primarily northern European descent which has experienced very low consanguinity (Jorde 1989), no evidence of founder effect (McLellan et al 1984), and heterozygosity similar to that of other populations of European ancestry (Xing et al 2009a). A previous study identified several related pairs of individuals in the Utah and non-Utah CEPH pedigrees (Stevens et al 2012), but only one mating pair used in our study had detectable consanguinity, with a coefficient of relationship of 0.001. Here, we present our findings of de novo L1, SVA, and Alu retrotransposition events in these pedigrees using three MEI-calling tools: MELT (Gardner et al 2017), RUFUS (https://github.com/ jandrewrfarrell/RUFUS) (Ostrander et al 2018), and TranSurVeyor (Rajaby and Sung 2018).…”
mentioning
confidence: 63%
“…The maxi-mum F ped was 0.40625 (n = 3). Thus, the degree of inbreeding within the colony is far greater than what has been observed in human populations (McQuillan et al 2008;Bittles and Black 2010;Stevens et al 2012).…”
Section: Comparison Of Pedigree-based and Genomic Estimates Of Inbreementioning
confidence: 87%
“…IBD detection methods are useful in many contexts such as identifying phasing errors or polymorphic deletions, estimating heritability, 7 , 43 inferring kinship 4 , 38 , 44 , 45 , 46 and mapping diseases in association studies. 47 , 48 In cases, where genealogical information is not available we now know that IBD is an alternative to account for unknown relatedness.…”
Section: Discussionmentioning
confidence: 99%